Multiswitching Synchronization of a Driven Hyperchaotic Circuit Using Active Backstepping. (18th February 2014) - Ajayi, A. Ayotunde; Ojo, S. Kayode; Vincent, E. Uchechukwu; Njah, N. Abdullahi
Abstract : An active backstepping technique is proposed for the realization of multiswitching synchronization of periodically forced hyperchaotic Van der Pol-Duffing oscillators. The active backstepping technique is a systematic design approach with recursive procedures that skillfully optimizes the choice of Lyapunov functions and active control technique. Using the active backstepping technique, the usual master-slave synchronization scheme is extended to study the synchronization of systems with different combinations of the slave states variables with master state variables. Our numerical results confirm the effectiveness of the proposed analytical technique.